1998
DOI: 10.3109/10425179809105210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Elicitin Gene Cluster inPhytophthora Cinnamomi

Abstract: Elicitins are a group of highly conserved proteins secreted by species of Phytophthora and a species of the related genus Pythium, Pythium vexans. Some of these proteins act as inducers of the necrotic hypersensitive-like response and the associated systemic acquired resistance phenomenon, in some species. We cloned and characterised the cinnamomin-beta and -alpha genes and two related elicitin genes from Phytophthora cinnamomi. These four open reading frames (ORFs) are clustered in tandem pairs. Two out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…In P. cinnamomi a gene cluster consisting of four elicitins genes was identified (Duclos et al, 1998) and the crystal structure of cinnamomin was determined (Rodrigues et al, 2006). The elicitin α-cinnamomin was shown to restrict the invasion of P. cinnamomi in root cortical tissues, preventing vascular colonization of cork and holm oak (Medeira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In P. cinnamomi a gene cluster consisting of four elicitins genes was identified (Duclos et al, 1998) and the crystal structure of cinnamomin was determined (Rodrigues et al, 2006). The elicitin α-cinnamomin was shown to restrict the invasion of P. cinnamomi in root cortical tissues, preventing vascular colonization of cork and holm oak (Medeira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in two other Phytophthora species also demonstrated clustering of elicitin genes. In both, P. cinnamomi and P. cryptogea, a 6-kb genomic region encompasses four elicitin genes (Panabieres et al 1995;Duclos et al 1998). In P. infestans the inf1 gene is highly expressed in mycelium but not in sporangia or cysts (Kamoun et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The deduced peptide comprised 119 aa, including the peptide signal sequence, and displayed a predicted pI of 3.95. From alignment with known elicitin sequences, it was considered to belong to class II of highly acidic elicitins and was accordingly called HAE1 (11,26).…”
Section: Resultsmentioning
confidence: 99%
“…Although elicitin genes are not appropriate for phylogenetic studies because of their multigenic family feature, they can be used as a tool for identification purposes since the amino acid sequence of a given elicitin may provide a signature at the species level (25). In addition, the 3Ј untranslated regions (3ЈUTRs) of class I elicitin genes are strictly conserved within an individual species but diverge between species to such an extent that sequence alignment is almost impossible (1,6,11;Panabières et al,unpublished results).…”
mentioning
confidence: 99%